The prevalence comparison of iron deficiency anemia (IDA) between non-elderly and elderly, study in rural areas of Ubon Ratchathani and Si Sa Ket Province - Seansing, Pattamaphorn; Vanichakulthada, Nawinda; Pinyachat, Anuwat (Health Science, Science and Technology Reviews, 2023)
There has never been a report comparing iron deficiency anemia between working age groups and elderly people living in the lower northeastern region of Thailand before. This research studied two sample groups: working people aged 18-59 years (146 people) and elderly people aged 60 years and over (147 people). The sample lived in rural areas in Ubon Ratchathani and Si Sa Ket provinces, where the prevalence of anemia was found to be high and caused by various causes. We use the 2022 World Health Organization (WHO) criteria to diagnose anemia using Hemoglobin (Hb) concentration. We use serum ferritin to indicate the amount of iron stored in the body and a C-reactive protein (CRP) test to indicate inflammation, both of which are used to diagnose iron deficiency. The results of the study found that the prevalence of anemia in the working age group compared to that in the elderly group was 39.7% and 58%, respectively, with the prevalence of anemia increasing with increasing age. The prevalence of iron deficiency in the working age group compared to the elderly group was 18.7% and 6%, respectively. Although iron deficiency anemia was found in working age people at 12.3%, more than in the elderly at 3.4%. However, anemia is found more in the elderly than in working people, which means that anemia in the elderly may be caused by other factors such as inflammation, chronic disease, malnutrition, abnormal iron absorption, etc. The median amount of iron stored in the body in the working age group was significantly lower than that in the elderly group (median 128.91 and 164.96 µg/L, respectively). This data indicates that serum ferritin, a type of acute phase protein, is released when the body is inflamed, especially in the elderly group. Therefore, diagnosing anemia among elderly people with chronic diseases is challenging. Future research to identify new markers to differentiate inflammation-related anemia from iron deficiency anemia is important.